2013
DOI: 10.4103/0253-7613.115015
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative effects of hesperetin against lead acetate-induced oxidative stress in rats

Abstract: Objectives:Oxidative stress with subsequent lipid peroxidation (LP) has been suggested as a mechanism for lead-induced toxicity. The current study was carried out to evaluate antioxidant activity of hesperetin against lead acetate-induced oxidative stress.Materials and Methods:The male rats were treated with hesperetin in combination with lead acetate (500 mg/L).Results:The results indicated that hesperetin alone did not induce any significant changes in the biochemistry of serum, liver, and kidney tissues. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 20 publications
(26 reference statements)
4
47
1
1
Order By: Relevance
“…Exposure to lead may alter antioxidant defense mechanism, which results in an imbalance Groups between radical-generating and radical-scavenging activities, and consequently, the formation of oxidation products. The finding of elevation in MDA concentration in lead exposed animals is consistent with the result obtained in previous studies (Aksu et al, 2012;Nisar et al, 2013;Wang et al, 2013;Okediran et al, 2017), verifying that exposure to lead causes an increase in MDA concentration. The significant increase in MDA concentration produced by exposure to lead suggests an increase in lipid peroxidation, which is an indicator to increased levels of free radicals in the serum and tissues of lead exposed rats.…”
Section: Discussionsupporting
confidence: 92%
“…Exposure to lead may alter antioxidant defense mechanism, which results in an imbalance Groups between radical-generating and radical-scavenging activities, and consequently, the formation of oxidation products. The finding of elevation in MDA concentration in lead exposed animals is consistent with the result obtained in previous studies (Aksu et al, 2012;Nisar et al, 2013;Wang et al, 2013;Okediran et al, 2017), verifying that exposure to lead causes an increase in MDA concentration. The significant increase in MDA concentration produced by exposure to lead suggests an increase in lipid peroxidation, which is an indicator to increased levels of free radicals in the serum and tissues of lead exposed rats.…”
Section: Discussionsupporting
confidence: 92%
“…Also, it can protect the cells from damage induced by I/R 74 . It has reported that HES treatment increased SOD, CAT and GSH-Px activities and reduced the tissue damage caused by oxidative stress-induced ischemia and I/R 75 . It was suggested that HES has positive effects on SOD, CAT and GSH-Px activities and has protective effects against oxidative stress in rat brain 76 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, BV aqueous extract could mitigate oxidative stress by increasing GSH level through scavenging H 2 O 2 as it was demonstrated by Gurer and Ercal [4] . BV polyphenols might be the potential agents in the chelating processes [40][41] .…”
Section: Resultsmentioning
confidence: 99%